Asymmetric Dimethylarginine in Patients with Ascending Aortic Aneurysms - Gavriliuk, Natalia D.; Druzhkova, Tatiana A.; Irtyuga, Olga B.; Zhloba, Alexandr A.; Subbotina, Tatiana F.; Uspenskiy, Vladimir E.; Alexeyeva, Nina P.; Moiseeva, Olga M. (AORTA, 2016)
Background: Ascending thoracic aortic aneurysm (aTAA) is a heterogeneous group of disorders that involve impaired endothelial function. The nitric oxide (NO) synthase inhibitor asymmetric dimethylarginine (ADMA) serves as an endothelial dysfunction marker. Thus, we investigated ADMA levels in patients with aTAA.Methods: Eighty-six patients with aTAA and 18 healthy individuals were enrolled. All patients underwent echocardiography. Plasma ADMA levels were measured using high-performance liquid chromatography.Results: ADMA levels were higher in aTAA patients than in control patients (p = 0.034). According to the multivariable regression model, higher ADMA levels were associated with ascending aortic diameter (p = 0.017), smoking (p = 0.016), and log-transformed estimated glomerular filtration rate (eGFR, p = 0.005).Conclusion: This pilot study demonstrates an association of ADMA with ascending aortic dilatation; however, further studies are needed to investigate whether increased ADMA levels underlie aTAA development.
Keywords: Asymmetric dimethylarginine; Thoracic aortic aneurysm; Endothelial dysfunction